1997
DOI: 10.3109/08860229709037213
|View full text |Cite
|
Sign up to set email alerts
|

The SHR as a Small Animal Model for Radiocontrast Renal Failure. Relation of Nephrotoxicity to Animal's Age, Gender, Strain, and Dose of Radiocontrast

Abstract: The male spontaneously hypertensive rat (SHR) Duarte, Zhang, and Ellis induced renal damage (RC-RD) increased as the animals aged. In addition, when the administered dose of RC was repeated a f e r a short interval of only 6 h, the degree of RC-RD increased greatly. In parallel control studies of the infruence of gender and strain on the response to &C in 12-month-old rats, neither hypertensive female SHR nor male normotensive Wstar-Kyoto (WKY) rats demonstrated signiJicant spontaneous renal pathology or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…16 An animal model using old spontaneously hypertensive male rats showed that high osmolar contrast media could enhance the progression of glomerulosclerosis and renal failure. 17 However, the long-term renal prognosis of patients after exposure to contrast media has not been reported well. In the Change in NAG at 24 h after angiography (%) 0.192 0.337…”
Section: Discussionmentioning
confidence: 99%
“…16 An animal model using old spontaneously hypertensive male rats showed that high osmolar contrast media could enhance the progression of glomerulosclerosis and renal failure. 17 However, the long-term renal prognosis of patients after exposure to contrast media has not been reported well. In the Change in NAG at 24 h after angiography (%) 0.192 0.337…”
Section: Discussionmentioning
confidence: 99%
“…The mean serum Cr concentration increased 0.025 mg/dl/day in older patients for 5 days after contrast exposure, while serum Cr did not increase in younger patients [32] . In the aging male SHR model for CI-AKI, old male rats (10, 12, or 14 months old) were more susceptible to developing CI-AKI than younger males (5 and 8 months old) [12] . In 14-month-old SHRs, urinary albumin excretion was markedly increased as a result of dysfunction of the glomerular capillary filter, increased glomerular albumin permeability, and presumably an increased number of more unselective pores in the glomerular barrier [33] .…”
Section: Similar Risk Factors For Ci-aki Shared By the Shr And Humansmentioning
confidence: 99%
“…This interaction is evident in SHRs exposed to contrast. These SHRs show an acute worsening of cardiac damage (apoptosis and necrosis of cardiomyocytes) contributing to CI-AKI, as demonstrated by glomerular necrosis and sclerosis, tubular cell apoptosis and necrosis, interstitial lymphocytic infiltration, and apoptosis of endothelial cells and smooth muscle cells in small vessels of the heart and kidney [12,15] .…”
Section: Preexisting Cardiac and Renal Damage In The Shr Closely Resementioning
confidence: 99%
See 1 more Smart Citation
“…The long-term renal effects of contrast media are uncertain; HO contrast media may enhance the progression of glomerulosclerosis and renal failure in old and spontaneously hypertensive male rats [38], but the longterm effects of contrast media on renal function in man are unknown.…”
Section: The Pathophysiology Of Cmnmentioning
confidence: 99%